Analisis Thermal Nilai Kalor Briket Ampas Batang Tebu dan Serbuk Gergaji - Wibowo, Rianto (Jurnal Rekayasa Mesin, 2019)
Availability of fossil fuels are increasingly rare, result in rising fuel prices. Hence, alternative fuel needs to be examined. In this study a mixed composition of bagasse charcoal and sawdust used. The two material then mixed with starch adhesives to produce briquettes with different compositions. This study aims to determine the thermal characteristics of briquettes with a variety of different compositions. This study uses a briquette composition variations sugarcane bagasse and sawdust 100%: 0%, 75%, 25%, 50%: 50%, 25%: 75%, and 0%: 100%. This type of research is the experimental method. Testing the thermal characteristics of charcoal briquettes bagasse and sawdust using a bomb calorimeter and boil a liter of water to determine the calorific value and the rate of combustion. The results showed that the briquettes with a variation of 100% : 0% has the highest calorific value of 4117 cal/gr and the lowest firing rate of 0,155 gr/min. Sawdust briquettes 100% has the lowest calorific value of 3657 cal/gr and the highest firing rate of 0,268 cal/g. There are differences in calorific value and the rate of combustion of charcoal briquettes bagasse and sawdust with a variety of different compositions. So it can be said that the longer the briquettes burning speed, the higher the value calorific